Do Wheat Grain Yield and Grain Protein Concentration Responses to Nitrogen Rate Depend on Variety-Specific Agronomic Traits? - Mariana Mota; Luiz O. Pradella; Jazmin Gastaldi; Jorge Romero Soler; Nicolas Giordano; Romulo P. Lollato (Kansas Agricultural Experiment Station Research Reports, 2025)
Nitrogen (N) management and genotype selection play crucial roles in optimizing winter wheat (Triticum aestivum L.) yield in Kansas. This study evaluated whether wheat cultivars with different agronomic traits would require differential nitrogen management. Eight cultivars were selected to represent high- and low-grain yield stability, above- and below-grain protein deviation for a given yield level, and early and late maturity. These cultivars were exposed to seven nitrogen rates ranging from 0 to 180 pounds of N per acre in seven rainfed locations in Kansas during the 2023–2024 growing season. Results suggested significant N rate by environment interactions and cultivar agronomic trait by environment interactions for grain yield and grain protein concentration. Still, there were no agronomic trait by N rate interactions. Overall, in specific environments, less stable cultivars outyielded more stable cultivars, and early maturity cultivars outyielded late maturity cultivars. These yield advantages were often associated with lower protein concentration. The agronomic trait of grain protein deviation did not result in yield advantages but had higher protein concentrations at all locations. These results emphasize the importance of understanding cultivar traits and their interaction with the environment when making variety selection, and the crop’s overall response to N management as a function of environmental conditions. Still, results suggested no differences in how N should be managed according to a cultivar’s specific agronomic traits.
Keywords: wheat variety; grain protein; nitrogen management